Physico-Chemical Characteristics of Smoked Catfish (Pangasius sp) Using a Multi-Tiered Drum Smoking Device and Corn Cobs as a Smoke Source - Fahrul, Fahrul; Syahrul, Syahrul; Nursab, Muhammad Hamka; Pratiwi, Putri Ayunda; Usman, Muhammad Syawal (Agrikan Jurnal Agribisnis Perikanan, 2024)
Catfish has advantages, but catfish also has disadvantages like other fish, namely it is quickly damaged. Smoking fish is one of the efforts to increase the shelf life and durability of fishery products through processing and preservation. This study aims to determine the organoleptic and chemical quality of smoked catfish which was conducted at the Fisheries Product Technology Laboratory (THP), Faculty of Marine Sciences and Fisheries (FIKP), Hasanuddin University (Unhas). Organoleptic testing was carried out at the Faculty of Maritime Affairs and Fisheries (FIKP), Hasanuddin University (Unhas). Smoked fish samples were taken from processors in Sidrap Regency using a purposive sampling method. The results showed that the organoleptic and chemical quality of smoked catfish with a source of corncob smoking for several parameters was in accordance with and not in accordance with SNI 2346:2011, namely organoleptic test (Â±6.57-7.5), SNI 2725: 2013, content water (49.00-63.10%), fat content (1.07-1.51%)